2013
DOI: 10.1371/journal.pone.0083799
|View full text |Cite
|
Sign up to set email alerts
|

Skin Autofluorescence Is Associated with the Progression of Chronic Kidney Disease: A Prospective Observational Study

Abstract: BackgroundAdvanced glycation end product (AGE) accumulation is thought to be a measure of cumulative metabolic stress that has been reported to independently predict cardiovascular disease in diabetes and renal failure. The aim of this study was to evaluate the association between AGE accumulation, measured as skin autofluorescence, and the progression of renal disease in pre-dialysis patients with chronic kidney disease (CKD).MethodsSkin autofluorescence was measured noninvasively with an autofluorescence rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 35 publications
1
30
1
1
Order By: Relevance
“…That study showed, in a cohort of 449 Japanese predialysis CKD patients with a 32% DM prevalence, that SAF predicted the rate of kidney function decline and incidence of end-stage kidney disease. 11 The discrepant findings in our study versus those in the study by Tanaka et al 22 may be because of population differences between the cohorts. For whites, the reference value of SAF in healthy individuals is 2.46±0.57 for the age group of 60 to 70 years, and SAF has been shown to increase with ≈0.023 AU per year.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…That study showed, in a cohort of 449 Japanese predialysis CKD patients with a 32% DM prevalence, that SAF predicted the rate of kidney function decline and incidence of end-stage kidney disease. 11 The discrepant findings in our study versus those in the study by Tanaka et al 22 may be because of population differences between the cohorts. For whites, the reference value of SAF in healthy individuals is 2.46±0.57 for the age group of 60 to 70 years, and SAF has been shown to increase with ≈0.023 AU per year.…”
Section: Discussioncontrasting
confidence: 89%
“…We found no association of SAF with eGFR decline in patients with PAD, which conflicts with earlier findings that showed a significant association of SAF with eGFR decline in patients with established CKD. 11 Therefore, the use of SAF as a predictor of kidney function decline may be limited to patients without cardiovascular comorbidity or SAF may only be a predictor in patients with established CKD. Further research is needed to clarify if, and in which populations, SAF can predict kidney function decline.…”
Section: Discussionmentioning
confidence: 99%
“…9 The predictive value of SAF for all-cause or cardiovascular mortality and cardiovascular events was previously shown in patients with PAD, diabetes mellitus, renal insufficiency, and myocardial infarction and for disease progression in chronic kidney disease. 10,[13][14][15][16] This study is the first to show that SAF is an independent predictor for leg outcome in patients with PAD. These results underscore the role of AGEs as predictor for progression of atherosclerosis beyond diabetes mellitus and renal insufficiency.…”
mentioning
confidence: 66%
“…AGEs serum levels have been associated to several vascular and neurological complications, especially in the cardiovascular field and a flourishing production of literature is pointing at AGEs as a marker of negative outcome in both diabetes management and surgical procedures on these patients (3,4). Detection and measurement techniques for AGEs have been gradually improved over the past 10 years starting from antibody and immune-based methods to the new readily available skin auto fluorescence techniques, which hold a promise for future bedside management of patients with diabetes (5). The reported role of AGEs in vascular complications of diabetes and cardiovascu-lar disease also prompted the development of pharmacological inhibitors of their effects, giving rise to many experimental activities and a number of both preclinical and clinical studies.…”
Section: Contextmentioning
confidence: 99%